Study of neodymium laser transition in glasses and influence of up-conversion processes under diode pumping - Courrol, Lilia Coronato; Kassab, Luciana Reyes Pires; Del Cacho, Vanessa; Wetter, Niklaus Ursus; Games, Laircio; Vieira Jr., Nilson Dias; Messaddeq, Yotines [UNESP]; Ribeiro, Sidney Jose L. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2003)
By solving the rate equations including upconversion for Nd glass hosts under continuous diode pumping, it was possible to calculate the nonlinear behavior of the pumping efficiency and threshold pump intensity as a function of exited-state population. © 2003 IEEE.